Outcome measurement in paediatric palliative care: lessons from the past and future developments - Downing, Julia; Namisango, Eve; Harding, Richard (Ann Palliat Med, 2018)
The need for paediatric palliative care (PPC) globally is great yet there is limited evidence of the quality or outcomes of the care provided. The lack of an outcome measure for PPC has been consistently cited as one reason for the lack of robust evidence in the field. Thus recommendations have been made for the development of locally relevant, validated tools to measure outcomes for children.This paper reviews relevant outcomes and quality measures in PPC, the current state of science on outcome measurement for children and young people (CYP) with life-limiting and life-threatening conditions and the development of the African Children’s Palliative Outcome Scale (C-POS). Lessons learnt from the past are presented before looking ahead at the need for future developments in outcome measures in PPC. A narrative review was undertaken and authors have drawn upon reflective insights from their collective experiences.Outcomes can be measured in a variety of ways, and due to the multi-dimensional nature of PPC, outcomes can be complex and hard to measure. Whilst there are a variety of outcome measures for use in adult palliative care, a similar range of tools does not exist in PPC. Literature reviews have confirmed the absence of a multi-dimensional PPC outcome measurement tool. Following on from their success in developing an outcome scale for adults in Africa, the African Palliative Care Association (APCA) have developed a multi-dimensional outcome tool for PPC—the African C-POS. Tool development and validation followed the COSMIN guidance. The draft C-POS consists of 12 questions, 8 in Section A for the child, and 4 in Section B for the parents/carers. The tool has been developed across eight African countries and is the first specifically designed, multi-dimensional outcome measure for PPC. Lessons have been learnt in the development of outcome scales in palliative care, including those specifically for PPC such as: undertaking research in PPC; the definition of PPC; if you ask a child what their concerns are they will tell you; do you use child and or proxy report? do you have different tools for different ages? what methods of scoring should be used? is it an outcome tool, an assessment tool or both? the length of the outcome measure; the length of time it takes to develop; and, it won’t be perfect. Whilst progress has occurred through the development of the C-POS there is still a long way to go in the development of outcome measures for PPC. Future developments include: finalization and publication of the African C-POS; utilization of the C-POS in clinical practice, research and audit; collation and review of data sets; and the development of C-POS in different settings.The measurement of outcomes in PPC is an imperative. Whilst there are challenges in developing outcome tools and utilizing them in practice, these should not prevent us from advancing the field. The development of the first outcome measure for PPC the African C-POS is a key milestone in the ongoing development and utilization of outcome measures for PPC.
Keywords: Patient reported outcome measures (PROMs); outcomes; palliative care; paediatrics; tools